A Study Effect of Hot Air Recirculating Ratio on Drying Behavior of Tilapia by Using a Hot Air Dryer Installed with Stainless Wire Mesh Porous Material - เหลือมพล รตินันท์; บุญจันทร์ สังวาลย์; อินลา คมเพ็ชร; กฤตาคม บัณฑิต (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This research aimed to study the effect of hot air recirculating ratio on behavior of tilapia drying by using a hot air dryer by installed with stainless wire mesh porous material. A present dryer was modified by co-operation of recirculating hot air and porous material at the inlet of drying chamber. In experiment, hot air temperature and velocity were maintained at 70 ºC and 2 m/s respectively. Hot air recirculating ratio (Cair) was varied by 0, 40, 60, and 80 %. Tilapia sliced was used as a drying product and mass of tilapia was recorded at interval 20 min during drying process until saturated mass condition. In this study, parameters considered of investigate the drying behavior were: dry basis moisture content (Md), moisture ratio (MR), drying rate (DR) and specific energy consumption (SEC). Thin layer drying models were also discussed in order to predict the drying behavior. From experimental result it was found that DR and Md were decreased as increasing drying time. DR was increased with Cair and Md. Drying time was varied between 420 - 440 min and the highest DR become 0.22 kgwater/min. SEC was decreased as Cair increased. The maximum reduction of SEC being 49.60 % was obtained at Cair = 80 %. The minimum SEC gave 3.14 MJ/kgwater evaporated at Cair = 80 %. For a study on thin layer drying models, the Modified Midilli model was most agreement with experimental result which R2 was more than 0.9964.